Evaluación del desempeño y su incidencia en el logro de la eficiencia empresarial de la empresa Terratecnica año 2021. - Nuñez Villalba, Betty Elizabeth (2022)
The present research project entitled: Evaluation of performance and its impact on the achievement of business efficiency of the Terratecnica company year 2021, has as a general objective Evaluate the impact of performance on the achievement of business efficiency of the Terratecnica S.A Company with the purpose to find the circumstances of the general problem of the Institution mentioned above and provide the possible solutions that allow solving said problems, being its main problem, how does the performance evaluation affect the business efficiency of the Terratecnica S.A Company? The design that was used in the development of this non-experimental research. To obtain information on the current state of the organization, research techniques such as interview, survey and observation were used, applying descriptive, inductive and deductive methods, which was carried out on the members of the organization to determine what is the incidence that exists in the company. Based on performance evaluation, with the purpose of determining the causes of the problem on the impact on the achievement of business efficiency. Based on the results obtained, the proposal of a model was established that allows to cover the shortcomings detected by not having a performance analysis that allows them to establish strategic objectives and to list the possible tasks to be carried out by the workers knowing their abilities and skills with in order to create training campaigns, design measures to improve performance, and therefore obtain good results.